Effect of diurnal temperature range on emergency room visits for acute upper respiratory tract infections - Jang, Jin Young; Chun, Byung Chul (Environmental health and preventive medicine, 2021)
An acute upper respiratory tract infection (URI) is the most common disease worldwide, irrespective of age or sex. This study aimed to evaluate the short-term effect of diurnal temperature range (DTR) on emergency room (ER) visits for URI in Seoul, Korea, between 2009 and 2013. Daily ER visits for URI were selected from the National Emergency Department Information System, which is a nationwide daily reporting system for ER visits in Korea. URI cases were defined according to International Classification of Diseases, 10 Revision codes J00-J06. The search for DTR effects associated with URI was performed using a semi-parametric generalized additive model approach with log link. There were 529,527 ER visits for URI during the study period, with a daily mean of 290 visits (range, 74-1942 visits). The mean daily DTR was 8.05 °C (range, 1.1-17.6 °C). The cumulative day (lag 02) effect of DTR above 6.57 °C per 1 °C increment was associated with a 1.42% (95% confidence interval [CI] 0.04-2.82) increase in total URI. Children (≤ 5 years of age) were affected by DTR above 6.57 °C per 1 °C, with 1.45% (95% CI 0.32-2.60) at lag 02, adults (19-64 years) with 2.77% (95% CI 0.39-5.20) at lag 07. When the DTR (lag02) was 6.57 °C to 11.03 °C, the relative risk was significant at 6.01% (95% CI 2.45-9.69) for every 1 °C increase in youth subjects aged for 6 to 18 years. DTR was associated with a higher risk for ER visits for URI. In addition, the results suggested that the lag effects and relative risks of DTR on URI were quite different according to age.